ANÁLISIS DE LA ESTRUCTURA COMUNICATIVA DEL GAD MUNICIPAL DE ZAMORA 2024 - Siranaula Zaruma, Gisela Cecibel (2025)
The present research analyzes the structure and communicative performance from GAD of Zamora Municipality with the objective of understanding its impact on citizens and suggest improvements in communication management. That is why specific objectives are identified, such as identifying the structure of the communication department, evaluating its performance, and analyzing the indicators of communicative impact. The methodology that was implemented for this study was a mixed approach, combining interviews with authorities and the communication team, and also with surveys directed to the citizens to know the perception and effectiveness of the messages issued. The results revealed that, although municipality communication is based on values of transparency and honesty, it lacks a formal communication plan, which represents a significant limitation, which limits the coherence and strategic planning of the messages. The interaction with the citizens is carried out mainly through social networks, but without any audience segmentation or impact evaluation strategies. It was identified that 42.6% of the population does not know about municipality projects, which show problems in the dissemination of key information. Likewise, 48.5% considers the municipality's communication to be either clear or confusing, reflecting the need to improve the style and structure of the messages. In terms of institutional reputation, 44.1% of respondents rated GAD’s management as average, which suggests that communication is not managing to strengthen the municipality image effectively. Therefore, it is known that the GAD Zamora's communication management must be strengthened through the implementation of a strategic communication plan, the creation of impact measurement indicators and the diversification of dissemination channels. In addition, it is recommended to establish a permanent evaluation model to adjust strategies based on the needs of the citizens